Characterization of Rubber Sack for Seating Evaluation System - Kim, W.D.; Bae, S.J.; Park, H.S.; Woo, C.S. (Asian Journal of Chemistry, 2013)
A flexible and stretchable rubber sack is used as a seating evaluation system to measure the figures and postures of people. A rubber sack filled with plastic pellets are prepared by folding and adhesion with a thin rubber sheet. For better design architectures, the rubber sheet requires a lower modulus and higher elongation because of the easy stretch and stretch and flexible deformability. In addition, the adhesion strength is an important quality factor of a rubber sack to guarantee the reliability of the system. Furthermore, the resistance of movement of the pellets should be reduced to obtain good deformability. This study found that the adhesive strength of an overlapped type rubber sack was more than 10 times higher than that of a butted type rubber sack. The flexibility and deformability of rubber sacks with oily pellets was more than double those with non-oily pellets. Overall, the performance and reliability for a seating evaluation system can be improved using a rubber sack filled with oily pellets.